IMPLEMENTASI SIGAP STRES TERHADAP KETERAMPILAN KELUARGA MERAWAT HIPERTENSI DI KABUPATEN PRINGSEWU - Purwono, Janu; Rianti, Dian Asih; Supriyanto, Heru; Sari, Rita (Coping: Community of Publishing in Nursing; Vol 11 No 3 (2023): Juni 2023, 2023)
The prevalence of hypertension in the world in 2017 based on statistical data from the American Health Institute reached 45,6% with the highest percentage in Africa. Data Lampung Province in 2020 showed the prevalence of hypertension is 29,94% and Pringsewu District has a hypertension prevalence of 10,74%. Hypertension is the top 10 diseases in Pringsewu Regency, Pringsewu Regency in 2020 with a prevalence of 26,56%. The family as part of the community is the entry point for nursing services, including hypertension. Management of hypertension can be done through lifestyle modification and stress management through progressive muscle relaxation. The purpose of this study was to find out if education on lifestyle modification and progressive muscle relaxation had an effect on family skills in caring for family members with hypertension. The research design used pre-experimental, with the one group pretest posttest design. The sampling technique used purposive sampling. Implementation of lifestyle modification education and progressive muscle relaxation (SIGAP STRES) was given to 97 families treating hypertension, given 30 minutes per session for 8 sessions. Bivariate analysis using Paired T-Test. SIGAP STRES nursing interventions affect the ability of families to care for family members with hypertension (p value = 0,048). There is an influence of SIGAP STRES on the ability of families to care for family members with hypertension.